Pemanfaatan Game Monopoli Wayang untuk Meningkatkan Minat Belajar Bahasa Jawa pada Peserta Didik Kelas V di SD Negeri Kembangarum 03 Kota Semarang - Arsa, Ayyni Qamara Syarafa; Azzahra, Anggun Ayu; Baskara, Bintang Ayu; Selasih, Mayang Ayu; Agry, Feylosofia Putri (Jurnal Ilmiah Wahana Pendidikan, 2025)
Students' interest in learning Javanese language subjects in elementary schools tends to be low, especially in the fifth grade of Kembangarum 03 State Elementary School. This study aims to explore the effect of using educational game media “Monopoly Wayang Game” in increasing interest in learning Javanese language. This study uses mixed method research with a sequential exploratory approach that begins with qualitative data collection and analysis to explore the needs, perceptions of teachers, and characteristics of students, then continued with quantitative testing of the effectiveness of the media developed. The subjects of this study were 27 fifth grade students consisting of 13 male students and 14 female students. The results showed that the use of Puppet Monopoly Game was able to create a more fun and interactive learning atmosphere. The increase in learning interest can be seen from the learning interest questionnaire score which shows a significant increase. Thus, this learning media is proven effective in increasing interest in learning Javanese.